2006
DOI: 10.1007/s11104-005-5706-6
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Selenite Absorption Between High- and Low-Selenium Rice Cultivars and its Mechanism

Abstract: Two rice cultivars, Xiushui 48 and S. Andrea, with significant difference in selenium (Se) concentrations in brown rice grains, were chosen to study the Se absorption and its mechanism in excised roots. The results showed that the high-selenium cultivar Xiushui 48 absorbed higher amounts of Na 2 SeO 3 than low-selenium S. Andrea at different Se levels and treatment periods. It was found that Na 2 SO 3 markedly inhibited Na 2 SeO 3 absorption by the excised roots of both cultivars. This inhibition might be due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 36 publications
(31 reference statements)
8
88
4
3
Order By: Relevance
“…S3). In contrast, sulfate had a comparatively smaller influence on Se accumulation in Se[IV]-exposed roots, which is similar to reports for rice (Zhang et al, 2006) and tomato (Solanum lycopersicum; Asher et al, 1977). Second, for roots supplied with Se[VI], a rapid accumulation of Se occurred within 30 min within the endodermis and cortex, especially in the more proximal root tissues (Fig.…”
Section: Uptake and Distribution Of Sesupporting
confidence: 86%
“…S3). In contrast, sulfate had a comparatively smaller influence on Se accumulation in Se[IV]-exposed roots, which is similar to reports for rice (Zhang et al, 2006) and tomato (Solanum lycopersicum; Asher et al, 1977). Second, for roots supplied with Se[VI], a rapid accumulation of Se occurred within 30 min within the endodermis and cortex, especially in the more proximal root tissues (Fig.…”
Section: Uptake and Distribution Of Sesupporting
confidence: 86%
“…The pH values of most soils in Enshi region are from acidic to neutral, about 4.5-6.5 (17,21), under which condition Se exists predominatly as selenite in well-drained soils (7). Relatively low pH could increase the absorption and accumulation of Se in rice (42). Se concentrations in different fractions of rice plants were rather different.…”
Section: Resultsmentioning
confidence: 99%
“…In paddy soil, Se is present in the form of selenite. A physiological study showed that selenite uptake by rice roots was inhibited by HgCl 2 and AgNO 3 , suggesting that aquaporin is implicated in the uptake of selenite (Zhang et al, 2006). However, the exact mechanism for selenite uptake has not been understood.…”
mentioning
confidence: 99%